PERSPEKTIF UMUM TENTANG PENYELESAIAN PERDEBATAN INTERNASIONAL YANG MENDUNIA - I Gusti Agung Ayu Wulandari (Jurnal Ilmu Hukum Sui Generis, 2022)
The reason for this research is to give an overall portrayal about the technique or method for worldwide debate goal that is being looked by nations. There are different ways for a country to pick the way their global debate to be settled and it relies upon every country to pick the goal techniques, whether the question will be settled through the worldwide court or through serene means. Different nations which are not connected with the debate are not permitted to impede different nations global debates settlement progress in any structure. The type of research in normative legal research. Library data in normative law, namely letters, books, adan official dokuments.